Beliefs of grade six learners' regarding adolescent pregnancy and sex - C. Grobler; Y. Botma; A.C. Jacobs; M. Nel (AOSIS, 2007)
Escalating adolescent pregnancy and risky sexual behaviour is becoming more common amongst young adolescents and especially amongst black adolescents in South Africa. Statistics confirm that South African adolescents as young as fourteen are already sexually active and become pregnant. The decision to become sexually active with resulting adolescent pregnancy whether planned or not, are directly influenced by the teenager's beliefs. A person's beliefs consist of a person' own individual beliefs or attitude as well as what the individual subjective norm which the individual perceive as other people's beliefs regarding the same object of reason. The aim of the study was to describe the attitude of black grade six learners under the age of fourteen, towards adolescent pregnancy and sex. A quantitative descriptive research design was used. Results were clustered according to demographic variables as well as beliefs that consist of attitude and subjective norm.